Environmental Literacy Level Students of the Faculty of Teaching and Educational Sciences Riau University - Erlinda, Sri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
Environmental problems are the responsibility of all of us. It is appropriate for a prospective teacher to have a high level of environmental literacy, especially if he has taken the mandatory courses in Environmental Science and Disaster Mitigation. Apart from that, students from the Faculty of Teacher Training and Education are expected to be able to increase their students' environmental literacy. This research aims to describe the level of environmental literacy of FKIP Riau University students. The population in this study was FKIP UNRI students, totaling 5,013 people, while the population was 20 people from 16 undergraduate study programs with a total of 320 people. The data collection techniques used were interviews, questionnaires, observation and documentation. Data were analyzed using frequency distribution techniques. The research results show that the level of environmental literacy seen from 4 indicators (knowledge, cognitive skills, attitudes and behavior) is in the